DDRE-20. GENERATION OF A HIGH-AFFINITY EGFR/EGFRvIII-TARGETED D2C7 CAR-T CELL. (9th November 2020) - Ryan, Katherine; Wilkinson, Daniel; Landi, Daniel; Fecci, Peter
Abstract: BACKGROUND: The intent of this investigation is to validate a novel, high-affinity epidermal growth factor receptor (EGFR) chimeric antigen receptor (CAR) T-cell product for adoptive immunotherapy of EGFR-expressing malignancies of the central nervous system (CNS). Wild type EGFR is ubiquitously expressed on glial tumors in both children and adults, and the majority of solid tumors that metastasize to the CNS but is not expressed on healthy CNS tissues. EGFR and its isoform mutant, EGFRvIII, are hyperactivated or overexpressed receptor tyrosine kinases described in many human cancers. D2C7 is a recombinant monoclonal antibody short chain variable fragment (scFv) that binds to both wild type EGFR and EGFRvIII. We hypothesize that D2C7 adapted as a CAR on primary human T cells will generate potent, cytotoxic activity against EGFR-expressing tumors in vivo. METHODS: In vitro interferon gamma release assays comparing the D2C7 CAR to the EGFRvIII CAR have proven that D2C7 CAR-T cells have high specificity and potent cytotoxicity against established murine glioblastoma (GBM) tumor cell lines, expressing both EGFR and EGFRvIII. Next steps include pre-clinical in vivo testing of the D2C7 CAR-T cells in murine models of CNS tumors expressing EGFR/EGFRvIII such as GBM, non-small cell lung carcinoma (NSCLC), breast carcinoma, and melanoma. CONCLUSIONS: To improve and validate the effectiveness of CAR T-cell therapy for EGFR-expressing CNS tumors, our team has designed a high-affinity CAR-T cell that targets both EGFRvIII and wild-type EGFR, known as a D2C7 CAR-T cell. This investigation has established pre-clinical anti-tumor activity of D2C7-CAR T cells in vitro and we plan to present more mature data regarding efficacy in orthotopic murine models of GBM, NSCLC, breast carcinoma, and melanoma at the meeting this Fall.